DETERMINAN TERHADAP KEPATUHAN WAJIB PAJAK MELALUI INFORMASI PERPAJAKAN SEBAGAI PEMODERASI - Anita, Anita Silvia Rahayu; Badjuri, Achmad (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2024)
The purpose of this research is to assess the use of e-filing, tax socialization, and tax knowledge on taxpayer compliance with tax information as a moderating variable for taxpayers at the West Semarang Pratama Tax Service Office (KPP). This research uses quantitative methods. This method uses a questionnaire as the basis for data collection. The population used in this research is Taxpayers registered at the West Semarang KPP. The sampling method used was purposive sampling with the criteria of taxpayers registered at the West Semarang KPP and using the e-filling application. In this research, the data analysis method used is Moderated Regression Analyze (MRA). The results of this research are that the use of e-filing and tax socialization has no effect on taxpayer compliance, but tax knowledge has a positive effect on taxpayer compliance, and tax information is not able to moderate the relationship between the use of e-filing, tax socialization, and tax knowledge on taxpayer compliance.